Kepastian Hukum Investasi Properti oleh Warga Negara Asing melalui PT Penanaman Modal Asing di Indonesia - Ligina Tesalonika; Diani Sadiawati; Aurora Jilena Meliala (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study analyzes legal certainty regarding property investment by foreign nationals through Foreign Investment Limited Liability Companies in Indonesia, as well as the ideal legal policy in regulating such investment activities. The issue arises from the increasing foreign investment in the property sector, while the legal framework governing property ownership through Foreign Investment Companies remains unclear and potentially creates legal uncertainty. This research employs normative legal research using statutory, conceptual, and case approaches. Legal materials were collected through library research on legislation, books, journals, and other relevant legal sources. The results show that the use of Foreign Investment Companies in property investment has not yet been supported by harmonized regulations between investment law and agrarian law in Indonesia. The absence of clear limitations regarding land tenure and property ownership through Foreign Investment Companies may lead to multiple interpretations and legal uncertainty for investors, the government, and society. The Rempang Eco-City project also demonstrates the importance of legal certainty in balancing investment interests, state control over land, and the protection of community rights. Therefore, clearer, harmonized, and legally certain regulations are necessary to ensure legal certainty in property investment while maintaining the nationality principle and the social function of land within the Indonesian agrarian law system.